Carbon Nanotube Based Fiber Supercapacitor as Wearable Energy Storage - Lu, Zan; Raad, Raad; Safaei, Farzad; Xi, Jiangtao; Liu, Zhoufeng; Foroughi, Javad (Frontiers in Materials, 2019)
Energy storage is a key requirement for the emerging wearable technologies. Recent progress in this direction includes the development of fiber based batteries and capacitors and even some examples of such fibers incorporated into prototype textiles. Herein we discuss the advantages of using the wet-spinning process to create nanostructured carbon based materials as wearable energy storage. The ability to control the physical, mechanical, electrical and electrochemical properties of carbon nanotube based fibers holds great promise to develop smart polymeric structure as an energy storing materials including fibers and textiles. This is the first comprehensive review to discuss effect of nanostructured energy materials on the electrochemical properties of carbon nanotube based fibers which covers the various compositions, spinning and fabrication conditions on the performance of wearable energy storage.